Optimized Resource Allocation for Distributed Joint Radar-Communication System - Ahmed, Ammar; Zhang, Yimin D. (IEEE transactions on vehicular technology, 2024)
In this article, we consider a distributed joint radar-communication (JRC) multiple-input multiple-output (MIMO) system that performs both radar and communication objectives simultaneously. By introducing radar and communication performance metrics, optimized power allocation is achieved for different transmitters of the JRC system. The objective of the radar subsystem is to achieve a desired target localization accuracy quantified in terms of the Cramer-Rao bound of the location estimates, whereas the objective of the communication subsystem is to improve the classical Shannon capacity. First, we consider non-cooperative radar- and communication-centric operations, and the power allocations are respectively optimized for these cases. Next, we present two novel resource allocation strategies for the cooperative JRC system. In the first strategy, joint resource optimization for radar and communication subsystems is performed by exploiting the same waveform resources, resulting in high spectrum efficiency. The second approach provides enhanced flexibility by exploiting separate sets of waveforms that are respectively dedicated to the radar and communication subsystems, enabling the JRC system to independently change radar subsystem waveforms based only on the radar surveillance profile, without impacting the communication subsystem waveforms. Simulation results clearly demonstrate significant performance gain of the proposed cooperative JRC system over radar- or communication-centric power allocation schemes.